Perbandingan Kualitas Hidup Lansia Di Panti Sosial Tresna Werdha Dengan Lansia Di Keluarga - Putra, Iqbal Prasetya; -, Agrina -; Utami, Gamya Tri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of study was to compare the quality of life between the elderly people who live in nursing home and elders who live with family. The research method used comparative study. The study was conducted in two population were in nursing home Khusnul Khotimah Pekanbaru on 30 elderly using total sampling and in Labuh Baru Barat village on 30 elderly using purposive sampling. The instrument of the research used a questionnaire have a validity the questionnaire is WHOQOLBREF. The analysis used was univariate using frequency distribution and bivariate analysis using T independent tests. The results of research about quality of life showed that elderly who lived with family have high qulity of life more than elderly in nursing home were 16 elderly (53,3%) in nursing home  and 13 elderly (43,3%) in family. Based on the statistical tests (T independent) results, it is concluded that there is no difference between quaity of life between  elderly people living in nursing home and elderly who lived with family (ρ value 0,198). Based on the result of this result, it is expected to family for give  caring to elderly people and suport that optimal like a give suporting elderly people for routine visite to social service.   Keywords: Elderly, Family, Quality of life, Social Institution